2014
DOI: 10.1097/dcr.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Internet Patient Information on Colorectal Cancer Surgery

Abstract: The quality of online patient information regarding colorectal cancer treatment is highly variable, often incomplete, and does not adequately convey the information necessary for patients to make well-informed medical decisions regarding treatment for colorectal cancer. An opportunity exists for professional medical societies to create more comprehensive online patient information materials that may serve as a resource to physicians and their patients (see Video, Supplemental Digital Content 1, http://links.lw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 15 publications
3
83
0
7
Order By: Relevance
“…Conversely, more effort was made to describe the effects and benefits of treatment. This is a fairly known problem with online cancer information [20][21][22][37][38][39] which makes reporting one-sided and thus withholds important information for treatment decision-making. However, this may not apply to all websites considered.…”
Section: Principal Results and Comparison With Prior Workmentioning
confidence: 99%
“…Conversely, more effort was made to describe the effects and benefits of treatment. This is a fairly known problem with online cancer information [20][21][22][37][38][39] which makes reporting one-sided and thus withholds important information for treatment decision-making. However, this may not apply to all websites considered.…”
Section: Principal Results and Comparison With Prior Workmentioning
confidence: 99%
“…For further analyses, we grouped the overall DISCERN scores into five categories: very poor (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), poor (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), moderate (39-50), good (51-62), and excellent (63-75). 32 Completeness was assessed by calculating the proportion of key elements, defined a priori, covered by each website.…”
Section: Scoring Of Quality and Completeness Of Information Presentedmentioning
confidence: 99%
“…36,37 This instrument has also been tested for use in assessing health information available on the Internet. 38 In this study, 'treatment choices' were caesarean section versus vaginal delivery.…”
Section: Data Extractionmentioning
confidence: 99%
“…an American survey defined around 32% of the websites to contain information of good or excellent quality while almost 60% were pointed out to be of poor quality [25]. In addition, Grewal et al [26] found that most websites are readable but potentially unreliable.…”
Section: Introductionmentioning
confidence: 99%